Integrated Payment Systems: Safeguarding Transactions and Elevating Service in Petro Retail - Santanu Purohit; Sujoita Purohit (Business, Management and Economics: Research Progress Vol. 7, 2024)
Customer buying habits have evolved significantly with the rise of technology adoption, especially in retail. This shift is particularly noticeable in petro retailing in India, where technology has begun to shape consumer experiences. However, alongside this progress, there has also been a notable increase in reported incidents of fraud affecting customers over the past few years. While technology has been integrated into petro retailing, there remains a gap in addressing these fraudulent activities, which, in turn, negatively impacts customer satisfaction and tarnishes the brand image of service providers and the industry as a whole. This study focuses on the implementation of an "Integrated Payment Mechanism" designed to ensure customers make accurate payments for their fueling services. Feedback was collected through a quantitative questionnaire, with survey samples gathered using a convenience sampling method. The results indicated that this technology-driven solution significantly improves the efficiency of the fueling process, reduces fraud by enabling multiple payment methods, and provides a "proof of service" via SMS confirmation. By minimizing customer grievances, the solution enhanced overall customer satisfaction. The findings from this study have been instrumental in redesigning the service landscape and bridging service gaps through a technology-led approach. Given the sharp increase in the usage of digital payment methods by customers and the increase in fraud customers, Oil Marketing Companies in India should adopt an integrated payment mechanism across all the fuel stations for a uniform experience for the customers. This shall help in the reduction of frauds with enhanced usage of digital payment.